2021
DOI: 10.1590/1809-2950/20028528042021
|View full text |Cite
|
Sign up to set email alerts
|

The effects of neuromuscular electrical stimulation on strength, pain, and function in individuals with knee osteoarthritis: a systematic review with meta-analysis

Abstract: We aimed to investigate the effects of neuromuscular electrical stimulation on muscle strength, pain relief, and improvement in function in patients with knee osteoarthritis. Databases were searched from December 2017 to July 2020 and included PubMed, Embase, LILACS, and the Cochrane Central Register of Controlled Trials. A manual search was also performed by checking the reference lists of eligible articles. The PRISMA guidelines were followed. The studies selected compared NMES with an exercise program on is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…All other studies that have investigated the effect of EMSmostly the term neuromuscular electrical stimulation (NMES) is used in literaturein knee OA have only used a local stimulation. The results of two recent meta-analysis on the effect of local EMS in individuals with knee OA indicate an increase in quadriceps muscle strength [52], but no significant reduction in pain [21,52].…”
Section: Discussionmentioning
confidence: 99%
“…All other studies that have investigated the effect of EMSmostly the term neuromuscular electrical stimulation (NMES) is used in literaturein knee OA have only used a local stimulation. The results of two recent meta-analysis on the effect of local EMS in individuals with knee OA indicate an increase in quadriceps muscle strength [52], but no significant reduction in pain [21,52].…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to investigate NMES only combined with exercise. In this sense, another systematic review found that NMES associated with exercise, compared to an active control group, increased isometric muscle strength of the quadriceps muscle in patients with knee OA, with very low‐certainty evidence (Bispo et al., 2021). Our review focused only on NMES combined with exercise, including other NMES alternatives such as superimposed on voluntary contractions and in a whole‐body configuration.…”
Section: Discussionmentioning
confidence: 99%
“…However, they have not analyzed the risk of bias. The only study that conducted such an assessment used the previous tool version (Bispo et al., 2021). Thus, one of this review's strengths is that it analyzed the risk of bias in studies based on outcomes deemed to be the most critical for decision‐making, as recommended by Cochrane (Flemyng et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations